Alkali-silica reaction in waterglass-activated slag mortars incorporating fly ash and metakaolin. (June 2018) - Shi, Zhenguo; Shi, Caijun; Zhang, Jian; Wan, Shu; Zhang, Zuhua; Ou, Zhihua
Abstract: Mitigation of alkali-silica reaction (ASR) in concrete is essential for durable and sustainable constructions. In conventional Portland cement-based concrete, alumina-rich supplementary cementitious materials such as low-calcium fly ash and metakaolin have been successfully used to mitigate ASR. Such effect has not been investigated for alkali-activated slag based materials. In this study, ASR expansion, changes in mortar weight and pore solution alkalinity have been studied. XRD and SEM/EDX have been employed to examine the reaction products and degradation of aggregates. The results demonstrate that there is an optimum dosage of fly ash to reduce ASR expansion of the studied mortars, whereas ASR expansion decreases with increasing the amount of metakaolin. It is found that the amount of ASR product formed is minor in the studied mortars with highest expansion. The pore solution alkalinity of the studied mortars is the main factor which controls the ASR in the alkali-activated slag mortars.